2015
DOI: 10.1088/1475-7516/2015/07/036
|View full text |Cite
|
Sign up to set email alerts
|

Scalar perturbations in cosmological models with dark energy-dark matter interaction

Abstract: Scalar cosmological perturbations are investigated in the framework of a model with interacting dark energy and dark matter. In addition to these constituents, the inhomogeneous Universe is supposed to be filled with the standard noninteracting constituents corresponding to the conventional ΛCDM model. The interaction term is chosen in the form of a linear combination of dark sector energy densities with evolving coefficients. The methods of discrete cosmology are applied, and strong theoretical constraints on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…This is the main result of the present investigation, and it is in agreement with the results of other observational works [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], however it has been arisen through the novel use of the recently released cosmic chronometers data.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is the main result of the present investigation, and it is in agreement with the results of other observational works [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], however it has been arisen through the novel use of the recently released cosmic chronometers data.…”
Section: Resultssupporting
confidence: 92%
“…Hence, many different scenarios of interacting dark energy have been constructed (see [7,8] for reviews and references therein). Interestingly enough, recently it has been shown that the current data might favor the late-time interaction between CDM and the vacuum energy [9][10][11][12] or the dynamical dark energy sector [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We note that coupled states of perfect fluids were investigated in the case of a perfect fluid with a constant equation of state parameter [25] and for the following cosmological scenarios and constituents of the Universe: quark-gluon nuggets [27], the CPL model [28], Chaplygin gas [29], nonlinear f (R) gravity [30], as well as the models with a scalar field [31,32] and dark sector interactions [33,34].…”
Section: Equations For Gravitational Potential φmentioning
confidence: 99%
“…Hence, in the literature one can find many such interacting scenarios (see [5,6] for review and references therein), independently of the specific dark-energy nature, namely whether it arises from fields [7,8] or through a gravitational modification [9,10,11]. The interacting scenarios can be very efficient in describing late-time universe, and moreover they seem * Electronic address: supriya.maths@presiuniv.ac.in † Electronic address: d11102004@163.com ‡ Electronic address: cs12ip026@iiserkol.ac.in § Electronic address: msaridak@phys.uoa.gr to be slightly favored comparing to non-interacting ones [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Additionally, they seem to be efficient in addressing the H 0 tension [30,31,32,33,34] as well as the σ 8 tension [34,35,36].…”
Section: Introductionmentioning
confidence: 99%